Identification of Saccharomyces cerevisiae proteins that bind to nucleosomes at positions other than the N-terminal histone tails - Jooste, Judith Elizabeth (University of the Free State, 2015)
Mutation studies have shown that the nucleosome surface is extremely important for proper DNA replication, transcription, chromatin remodelling and thus correct gene expression. Therefore it is expected that these surfaces of the nucleosome would bind some of the arsenal of regulatory proteins available in the cell. Despite the obvious functional importance of the nucleosome cores, little is known with regards to possible binding partners. A few interactions with the nucleosome surface has been studied. Silent Information Regulator protein 3 (SIR3) is grouped in a family of chromatin regulators thought to facilitate transcriptional silencing via compaction of chromatin. Two viral proteins have also been shown to interact with chromatin by binding the acidic pocket formed by the H2A-H2B dimer. These are the latency-associated nuclear antigen (LANA) of Kaposi’s sarcoma-associated herpesvirus and the 72kDa immediate early 1 (E1) protein of human cytomegalovirus. The nucleosome core surfaces are thus also assumed to play key roles in infectious cycles of these and possibly more viruses. Other known binding partners include members of the high mobility group (HMGN) proteins and regulator of chromosome condensation 1 (RCC1). These proteins play vital roles in the regulation of chromatin structure and thus DNA accessibility. By identifying the binding partners of the nucleosome cores we will advance our understanding of the regulatory mechanisms of chromatin which will aid in understanding the onset and progression of many diseased states. This study aimed to identify proteins which bind to the non-tail parts of the nucleosome to further our understanding of the regulation of DNA function. To this end Xenopus laevis histones were expressed in Escherichia coli, both as full-length, canonical histones as well as N-terminally truncated globular domains. These were reconstituted with a biotinylated DNA-fragment to pull down any proteins bound to the histone octamers following incubation with a nuclear extract from Saccharomyces cerevisiae. The resulting proteins were identified when analysed by nanoLC-MS/MS and searched against the SwissProt database using Mascot. In total 25 nuclear proteins were identified to bind exclusively to the globular domain of the nucleosomal core particle. The results obtained provide a good starting point for further computer simulation studies as well as directed approaches to study specific interactions in vivo.

Mutasiestudies het gewys dat die nukleosoomoppervlak belangrik is vir suksesvolle DNA replisering, transkripsie, chromatien hermodellering en gevolglik korrekte geenuitdrukking. Dit word dus verwag dat hierdie oppervlaktes van die nukleosoom sekere lede van die regulatoriese proteïengroep sal bind. Ten spyte van die ooglopende funksionele belang van die nukleosoom se globulêre domein is min inligting beskikbaar oor moontlike proteïen-interaksies. Die Silent Information Regulator proteïen 3 (SIR3) groepeer onder ‘n familie van chromatienreguleerders wat vermoedelik transkripsie onderdruk deur middel van chromatienkompaktering. Twee virale proteïene, Latency-Associated Nuclear Antigen (LANA) van die Kaposi se sarkoomverwante herpesvirus en Immediate Early 1 (E1) proteïen van die menslike sitomegaalvirus, is ook bekend daarvoor om met chromatien se suurresidues op die H2A-H2B dimeer se oppervlak te bind. Die nukleosoom se globulêreoppervlaktes word dus moontlik geïmpliseer in ‘n sleutelrol in die infeksiesiklus van hierdie en moontlik ander virusse. Ander proteïene met bekende interaksies met die nukleosoomoppervlak sluit in lede van die High Mobility Group (HMG) proteïene sowel as die Regulator of Chromosome Condensation 1 (RCC1). Hierdie proteïene speel belangrike rolle in die regulasie van chromatienstruktuur en dus DNA toeganklikheid. Deur verdere identifisering van proteiene wat die globulêre areas bind word die kennis rondom chromatienreguleringsmeganismes uitgebrei. Kennis hieromtrent kan lei tot ‘n beter begrip van die aanvang en ontwikkeling van siektetoestande en sal bydra tot ‘n beter begrip van die regulasie van DNA-funksies. Hierdie studie het gepoog om proteïene wat die globulêre nukleosoomareas bind te identifiseer. Hiervoor is Xenopus laevis histone (ongemodifiseerde sowel as globulêre histone waarvan die N-terminale areas afgesny is) in E.coli uitgedruk en met ‘n gebiotinileerde DNA-fragment hersaamgestel. Op hierdie wyse is die hersaamgestelde oktamere en enige proteïene wat hulle sou bind tydens inkubasie met ‘n Saccharomyces cerevisiae kernekstrak afgetrek. Die afgetrekte proteïene is met nanoLC-MS/MS geanaliseer en met Mascot vanuit die SwissProt databasis geidentifiseer. In totaal is 25 kernproteiene geidentifiseer wat uitsluitlik aan die globulere domein area van die NCP bind. Die resultate verkry bied ‘n goeie wegspringpunt vir verdure ondersoeke met rekenaargebasseerde simulasies en meer direkte in vivo studies.
Dissertation (M.Sc. (Microbial, Biochemical and Food Biotechnology))--University of the Free State,2015
Keywords: Protein binding; Binding sites (Biochemistry)